Flying deep : climb inside deep-sea submersible Alvin - Cusolito, Michelle (Charlesbridge, 2018)
"Climb aboard Alvin, the famous deep-sea submersible credited with helping to find the Titanic, and take a trip two miles down to the bottom of the ocean. Experience a day in the life of an Alvin pilot and join scientists at the seafloor to collect samples and conduct research. Along the way, discover what one wears, eats, and talks about during a typical eight-hour trip in a underwater craft and find out more about the animals that live deep in our oceans. Extensive back matter explains how Alvin works, describes the author's research, and includes a glossary and further reading."--Amazon.com.